An organic technology or a technological naturalness? The program of unifying technology and nature - Gloy, Karen; Domínguez Hernández, Javier (Estudios de Filosofía, 1993)
The article attempts to serve as an intermediary between two opposite positions: the one originating in a scientific, physical and mathematical, technical and technological concept of nature, and the one originating in an organological concept of the Lebenswelt. The attitude towards nature will be, according to the respective case, objectifying and domineering, or sympathetic and eco-ethical. The article shows the history of this opposition and pleads for a mental change that integrates man and nature in an organic whole.